The Impact of Geopolitical Risks on Global Supply Chains - The Example of the Palestinian-Israeli Conflict - Liu, Shuling (International Journal of Global Economics and Management, 2024)
Geopolitical risk is an international risk that transcends the borders of a single country, and in response to the diversity and suddenness of the types of geopolitical risk-causing indices, there are all kinds of uncertainties in the process of global supply chain management affected by geopolitical risk, which makes the main body of the supply chain affected by the risk. With the development of globalisation, more and more enterprises extend their production and supply chains to all parts of the world, which makes geopolitical risk one of the important challenges that they must pay attention to and deal with. Factors such as regional political instability caused by the Israeli-Palestinian conflict, disruptions in the transport of goods, the impact on regional supply chains, and volatility in financial markets all pose challenges to the stability and reliability of global supply chains.